Understanding love : philosophy, film, and fiction - Wolf, Susan R. (Oxford University Press, 2014)
This collection of original essays, written by scholars from disciplines across the humanities, addresses a wide range of questions about love through a focus on individual films, novels, plays, and works of philosophy. Many varieties of love are discussed, among them, friendship, romantic love, parental love, and the love of an author for her characters.